Genome-wide identification and expression analysis of diacylglycerol acyltransferase genes in soybean (Glycine max) - Shihui Zhao; Fan Yan; Yajing Liu; Monan Sun; Ying Wang; Jingwen Li; Xinsheng Zhang; Xuguang Yang; Qingyu Wang (PeerJ, 2023)
Background Soybean (Glycine max) is a major protein and vegetable oil source. In plants, diacylglycerol acyltransferase (DGAT) can exert strong flux control, which is rate-limiting for triacylglycerol biosynthesis in seed oil formation. Methods Here, we identified soybean DGAT genes via a bioinformatics method, thereby laying a solid foundation for further research on their function. Based on our bioinformatics analyses, including gene structure, protein domain characteristics, and phylogenetic analysis, 26 DGAT putative gene family members unevenly distributed on 12 of the 20 soybean chromosomes were identified and divided into the following four groups: DGAT1, DGAT2, WS/DGAT, and cytoplasmic DGAT. Results The Ka/Ks ratio of most of these genes indicated a significant positive selection pressure. DGAT genes exhibited characteristic expression patterns in soybean tissues. The differences in the structure and expression of soybean DGAT genes revealed the diversity of their functions and the complexity of soybean fatty acid metabolism. Our findings provide important information for research on the fatty acid metabolism pathway in soybean. Furthermore, our results will help identify candidate genes for potential fatty acid-profile modifications to improve soybean seed oil content. Conclusions This is the first time that in silico studies have been used to report the genomic and proteomic characteristics of DGAT in soybean and the effect of its specific expression on organs, age, and stages.